2020
DOI: 10.1002/est2.123
|View full text |Cite
|
Sign up to set email alerts
|

Trombe walls with phase change materials: A review

Abstract: Solar energy utilization for covering the heating loads of buildings is an innovative and clean way to reduce electricity consumption. A Trombe wall is a classical passive solar heating system used in buildings. Increasing the weights and volumes of Trombe walls can increase their heat storage capacities. However, this process increases a building's dead load, which is considered a problem by structural engineers. Among the alternatives for solving this problem is to use phase change materials (PCMs) for highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…Omara and Abuelnuor [54] reviewed the implementation of Tromb walls with PCMs. The review led the authors to conclude that the low-thermal resistance of the tromb wall could be mitigated through the incorporation of PCM, which exhibit high storage capacity, and hence the heat dissipation can be reduce and solar radiation gain could be better controlled.…”
Section: Pcm Integrated Trombe Wallsmentioning
confidence: 99%
“…Omara and Abuelnuor [54] reviewed the implementation of Tromb walls with PCMs. The review led the authors to conclude that the low-thermal resistance of the tromb wall could be mitigated through the incorporation of PCM, which exhibit high storage capacity, and hence the heat dissipation can be reduce and solar radiation gain could be better controlled.…”
Section: Pcm Integrated Trombe Wallsmentioning
confidence: 99%
“…One of the most common reasons that PV modules are ventilated through backside air gaps is the cooling of the PV cells, which improves their efficiency. The effect of cooling can be further increased by decreasing the overheating of PV cells by storing the heat in the phase change material [25,26], However, in the analyzed case, the BIPV in the form of a glazed façade, structures are built with relatively thick (4 to 5 mm) double-sided hard glass layers, using material with a relatively low thermal conductivity (g 0.76 W/mK). In addition, the PCM material has even lower thermal conductivity at 0.2 W/mK.…”
Section: Design Of Semi-transparent Building-integrated Photovoltaic-thermal Glazed Façade Structures (S-bipv/t)mentioning
confidence: 99%
“…Commonly, researchers report that cooling with latent heat storage improves the annual electricity production with PV and that such measures are also cost effective [25]. A literature review [26] reveals that PCM heat storage is most often placed on the backside of a BIPV. Indartono et al [27] used a 15 mm PCM layer with a PCM melting temperature range of 42-55°C on the backside of a PV module.…”
mentioning
confidence: 99%
“…From results, solar dual catalytic Trombe wall with traditional shapes of inlet and outlet showed a decrease in thermal efficiency with increasing channel width while there was no noticeable effect with the channel height. Omara and Abuelnuor [12] presented an extensive review on the various advantages of using PCMs Trombe walls. The article showed that heat storage capacity was adequate because PCM can…”
Section: Introductionmentioning
confidence: 99%